Paradoxes of providing rural social services: the case of homeless youth - Edwards, Mark Evan; Sattem, Jennifer; Torgerson, Melissa (2009)
Economic and demographic changes in rural areas continue to introduce big-city problems in small towns. These communities' ability and willingness to respond are likely to be influenced by the geography, culture, and array of organizations in rural places. But how these characteristics of rural places shape local response is hard to predict and as yet unexplored. This article reports data from interviews with social-service providers and homeless youth in a rural county in the northwestern United States, drawing insights from both groups about the challenges of providing social services in rural places. Findings about drug use, sexual abuse and prostitution in rural communities illustrate how aspects of a rural context can influence the way small towns address social problems. - Reproduced.
Keywords: Youth; Social services